Fetal Hemoglobin is Associated with Peripheral Oxygen Saturation in Sickle Cell Disease in Tanzania - Siana Nkya; Josephine Mgaya; Florence Urio; Abel Makubi; Swee Lay Thein; Stephan Menzel; Sharon E. Cox; Charles R. Newton; Fenella J. Kirkham; Bruno P. Mmbando; Julie Makani (EBioMedicine, 2017)
Fetal hemoglobin (HbF) and peripheral hemoglobin oxygen saturation (SpO2) both predict clinical severity in sickle cell disease (SCD), while reticulocytosis is associated with vasculopathy, but there are few data on mechanisms. HbF, SpO2 and routine clinical and laboratory measures were available in a Tanzanian cohort of 1175 SCD individuals aged ≥ 5 years and the association with SpO2 (as response variable transformed to a Poisson distribution) was assessed by negative binomial model with age and sex as covariates. Increase in HbF was associated with increased SpO2 (rate ratio, RR = 1.19; 95% confidence intervals [CI] 1.04, 1.37 per natural log unit of HbF; p = 0.0004). In univariable analysis, SpO2 was inversely associated with age, reticulocyte count, and log (total bilirubin) and directly with pulse, SBP, hemoglobin, and log(HbF). In multivariable regression log(HbF) (RR 1.191; 95%CI 1.04, 1.37; p = 0.013), pulse (RR 1.01; 95%CI 1.00, 1.01; p = 0.026), SBP (RR 1.008; 95%CI 1.00, 1.02; p = 0.014), and hemoglobin (1.120; 95%CI 1.05, 1.19; p = 0.001) were positively and independently associated with SpO2 while reticulocyte count (RR 0.985; 95%CI 0.97, 0.99; p = 0.019) was independently inversely associated with SpO2. In SCD, improving SpO2, in part through cardiovascular compensation and associated with reduced reticulocytosis, may be a mechanism by which HbF reduces disease severity.